2020
DOI: 10.1021/acssuschemeng.0c05549
|View full text |Cite
|
Sign up to set email alerts
|

Superionic Si-Substituted Lithium Argyrodite Sulfide Electrolyte Li6+xSb1–xSixS5I for All-Solid-State Batteries

Abstract: Lithium-based solid electrolytes have been investigated in many studies for improving the energy density and safety of conventional Li-ion batteries. Recently, Li argyrodites (Li6+x Sb1–x Si x S5I) have been reported as promising superionic conductors, exhibiting an ionic conductivity above 10 mS cm–1. This study examined the high ionic conductivities of Li6+x Sb1–x Si x S5I using first-principles calculations and subsequent experiments. The calculation results demonstrate that the Li ionic conductivities incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 47 publications
(77 reference statements)
4
39
0
Order By: Relevance
“…19 Experimental and theoretical studies demonstrated that the additional Li ions occupying the high-energy interstitial sites in Li 6+x Sb 1−x Si x S 5 I resulted in concerted Li-ion migration, leading to ionic conductivities that are 3 orders of magnitude higher than those of Li 6 SbS 5 I. 19,20 High ionic conductivities of up to 6.3 mS cm −1 (x = 0.4), attributed to the additional Li ions in the argyrodite phases, have also been observed in Ge-substituted argyrodites, Li 6+x Sb 1−x Ge x S 5 I. 19 Previous studies revealed that the synthesis process, which includes high-energy ball milling and thermal annealing, increased the solubility limit of Si and the ionic conductivity in Li 6+x Sb 1−x Si x S 5 I (13.1 mS cm −1 , x = 0.75).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…19 Experimental and theoretical studies demonstrated that the additional Li ions occupying the high-energy interstitial sites in Li 6+x Sb 1−x Si x S 5 I resulted in concerted Li-ion migration, leading to ionic conductivities that are 3 orders of magnitude higher than those of Li 6 SbS 5 I. 19,20 High ionic conductivities of up to 6.3 mS cm −1 (x = 0.4), attributed to the additional Li ions in the argyrodite phases, have also been observed in Ge-substituted argyrodites, Li 6+x Sb 1−x Ge x S 5 I. 19 Previous studies revealed that the synthesis process, which includes high-energy ball milling and thermal annealing, increased the solubility limit of Si and the ionic conductivity in Li 6+x Sb 1−x Si x S 5 I (13.1 mS cm −1 , x = 0.75).…”
mentioning
confidence: 94%
“…These trends are consistent with previous studies showing that additional Li ions in argyrodite structures by aliovalent substitution result in high ionic conductivity owing to concerted Li-ion migration. 19,20 Additional Li ions in high-energy sites between bipyramids facilitated consecutive Li-ion migration through the inter-cage path and reduced the activation energy of Li-ion migration. 19,20,50 Cyclic voltammetry (CV) was conducted to examine the electrochemical stability of Li 6.5 Sb 0.5 Ge 0.5 S 5 I with a cell configuration of Li | Li 6.5 Sb 0.5 Ge 0.5 S 5 I | Li 6.5 Sb 0.5 Ge 0.5 S 5 I/C.…”
mentioning
confidence: 99%
“…Recently, the lithium argyrodites Li 6 PS 5 X (X = Cl, Br, and I) have generated much interest with regard to higher ionic conductivity and ease of processing at room temperature. ,, It has been previously reported that aliovalent substitution of P with Si, Ge, and Sn, , the chalcogenides with O, S, and Se, , and different halides/enriched halides ,, in argyrodites can strongly affect the structure and result in significant changes in ionic conductivity. , Li 6 PSe 5 I is known to exist within space group F 3m, where the halide ions occupy a face-centered cubic lattice (Wyckoff 4 a ), with PSe 4 3– polyhedra on the octahedral sites (P on Wyckoff 4 b and Se 2– on Wyckoff 16 e ), and the Se 2– in half of the tetrahedral sites (Wyckoff 4 d ). The lithium ions occupy the T2 (Wyckoff 48 h ) and T5a (Wyckoff 24 g ) sites as shown in Figure . , …”
Section: Introductionmentioning
confidence: 99%
“…45 Lee et al introduced argyrodite sulfide electrolyte, Li 6+x Sb 1−x Si x S 5 I, which has a high ionic conductivity of 13.1 mS/cm and low activation energy of 0.17 eV for x = 0.75 members. 46 2.6. Li-Based Garnets.…”
Section: Lisicon and Nasiconmentioning
confidence: 99%